2007
DOI: 10.1007/s00439-007-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of full-length survival motor neuron by polyphenol botanical compounds

Abstract: The loss of survival motor neuron-1 (SMN1) is responsible for the development of the neurodegenerative disorder spinal muscular atrophy (SMA). A nearly identical copy of SMN1 is present on the same chromosomal region called SMN2. While SMN2 encodes a normal SMN protein, the majority of SMN2-derived transcripts are alternatively spliced, resulting in a truncated protein that lacks the 16 amino acids encoded by SMN exon 7. Numerous studies have shown that the SMN2-derived protein product, called SMNDelta7, is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 48 publications
5
33
0
Order By: Relevance
“…These results suggest that EGCG might influence pre-mRNA splicing of gp130 toward formation of mRNA transcripts that synthesize sgp130 and warrants further testing. This notion is further supported by recent studies in which EGCG was found to inhibit the loss of survival motor neuron-1 protein and also to produce a full-length functional protein by correcting an aberrant alternative mRNA splicing in the cells from familial dysautonomia patients (39,40). However, our study demonstrates that EGCG can induce alternative mRNA splicing to produce a truncated form (i.e., sgp130) with potent antagonistic activity.…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that EGCG might influence pre-mRNA splicing of gp130 toward formation of mRNA transcripts that synthesize sgp130 and warrants further testing. This notion is further supported by recent studies in which EGCG was found to inhibit the loss of survival motor neuron-1 protein and also to produce a full-length functional protein by correcting an aberrant alternative mRNA splicing in the cells from familial dysautonomia patients (39,40). However, our study demonstrates that EGCG can induce alternative mRNA splicing to produce a truncated form (i.e., sgp130) with potent antagonistic activity.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown its role in inhibiting adipose cell proliferation, lipid accumulation, and stimulation of apoptosis and lipolysis in mature adipocytes. Further, resveratrol is shown to modulate alternative splicing of pre-mRNA (30). However, its mechanisms of action and target proteins in apoptotic pathway during adipogenesis was not determined.…”
Section: Resultsmentioning
confidence: 99%
“…Although activation of AMPK by metformin, resveratrol, and berberine have been well documented, several naturally occurring AMPK-activating compounds have also been shown to correct aberrant alternative splicing in various disease states, including EGCG (corrected aberrant splicing of IKAP mRNA in cells from patients with familial dysautonomia) and curcumin (stimulated full-length production of SMN RNA and protein in patient fibroblasts, increasing the inclusion of exon 7 in SMN2 transcripts) [110][111][112][113]. Additionally, histone deacetylases (HDACs) have also been shown to modulate alternative splicing by influencing splice site selection [114].…”
Section: Additional Compounds Correct Splice Site Defects Via Ampk Acmentioning
confidence: 99%